Investigating the impact of mental rehearsal on prefrontal and motor cortical haemodynamic responses in surgeons using optical neuroimaging - Modi, Hemel N.; Osborne-Grinter, Maia; Patel, Ronak; Darzi, Ara; Leff, Daniel R.; Singh, Harsimrat (Frontiers in Human Neuroscience, 2024)
Introduction: Inadequate exposure to real-life operating can impede timely acquisition of technical competence among surgical residents, and is a major challenge faced in the current training climate. Mental rehearsal (MR) -the cognitive rehearsal of a motor task without overt physical movement -has been shown to accelerate surgical skills learning. However, the neuroplastic effect of MR of a complex bimanual surgical task is unknown. The aim of this study is to use functional near-infrared spectroscopy (fNIRS) to assess the impact of MR on prefrontal and motor cortical activation during a laparoscopic knot tying task. Methods: 12 surgical residents performed a laparoscopic knot tying task before and after either mental rehearsal (MR, intervention group) or textbook reading (TR, control group). In both groups, fNIRS was used to measure changes in oxygenated haemoglobin concentration (HbO2) in the prefrontal (24 channels) and motor cortices (22 channels). Technical performance was measured using leak volume, objective performance score and task progression score. Results: MR led to a decrease in HbO2 (reduced activation) in the bilateral prefrontal cortex (PFC), and an increase in HbO2 (increased activation) in the left middle frontal gyrus, left precentral gyrus, and left postcentral gyrus. No discernible changes in activation were observed after TR in either the PFC or motor cortex. Moreover, smaller ΔHbO2 responses in the right PFC and greater ΔHbO2 responses in the left motor cortex were observed in the MR group compared with the TR group. Leak volume was significantly less following MR (p=0.019), but not after TR (p=0.347). Mean objective performance score was significantly higher following MR compared with TR (p=0.043). Conclusion: Mental rehearsal may enhance surgical skill acquisition and technical proficiency by reducing utilisation of attentional resources in the prefrontal cortex and improving neural efficiency in motor areas during a laparoscopic surgical task.